Integrated extrusion molding method and equipment for high-performance nanofiber structural member

Through the integrated extrusion molding method of high-performance nanofiber structural parts, the problems of inaccurate structural control, adhesive failure under high temperature environments in the existing honeycomb paper preparation methods are solved, and the efficient preparation of high-quality and special-shaped fiber structural parts are achieved.

CN119704512AActive Publication Date: 2025-03-28SOUTH CHINA UNIV OF TECH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411766405.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-28
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing honeycomb paper preparation methods have problems such as inaccurate structural control, adhesive failure in high-temperature environments, shape limitations and environmental protection.

Method used

Using the integrated extrusion molding method of high-performance nanofiber structural parts, nanofiber solution is shear-mixed in a forced mixing conveying device and solvent exchange is performed in the molding mold to form a nanofiber composite gel with a predetermined shape.

Benefits of technology

It realizes efficient preparation of high-quality and special-shaped fiber structural parts, solves local unit defects, single molding shapes, and environmental protection problems in high-temperature environments, and has the ability to prepare complex spatial structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704512A_ABST
    Figure CN119704512A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fiber structural part preparation, in particular to an integrated extrusion molding method and device for a high-performance nanofiber structural part. The integrated extrusion molding method for the high-performance nanofiber structural member comprises the following steps: (1) adding a nanofiber solution into a forced mixing and conveying device, so that the nanofiber solution is sheared and converted into a homogenized dispersion liquid in the forced mixing and conveying device, then, the homogenized dispersion liquid is injected into a forming mold through an extrusion mold head under the extrusion pressure provided by a forced mixing and conveying device; (2) immersing the whole forming mold into a reconstitution solution, and performing solvent exchange on the homogenized dispersion liquid injected into the forming mold and the reconstitution solution to enable the homogenized dispersion liquid to generate sol-gel conversion so as to form nanofiber composite gel with a preset shape; and (3) washing and drying the nanofiber composite gel with the preset shape to obtain the nanofiber structural member. The method has the advantages of few procedures and small harm to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber structural component preparation, and in particular to an integrated extrusion molding method and equipment for high-performance nanofiber structural components. Background Art

[0002] High-performance fibers such as PBO fibers and aramid fibers have attracted widespread attention due to their excellent mechanical properties and extremely high decomposition temperatures. As one of the representatives of high-performance fibers, aramid fibers were first synthesized by DuPont in the United States in the 1970s. Due to its unique rigid molecular chain and a large number of intermolecular hydrogen bonds, aramid fibers have the characteristics of light weight, high strength, and high temperature resistance, and have been widely used in the military field. Through wet molding technology, aramid fibers can be made into high-performance sheet-like aramid paper materials, and these aramid papers can be further prepared into aramid honeycomb papers with special structural shapes through complex processes.

[0003] Aramid honeycomb paper (NOMEX honeycomb) is a high-performance bionic aramid structural component, which is composed of hexagonal units. This honeycomb paper not only inherits the excellent properties of aramid fiber such as high specific strength, fire retardancy, and chemical corrosion resistance, but also has unique capabilities such as high vibration absorption and high electromagnetic wave transmittance. Therefore, aramid honeycomb paper plays an important role in scenarios such as aerospace, rail transportation, military and national defense, which have extremely high requirements for light weight and high strength of materials.

[0004] PBO fiber is another representative of high-performance fiber, first invented by the U.S. Air Force aerodynamics researchers. Due to its unique molecular structure, PBO fiber has excellent strength, modulus, heat resistance and impact resistance. In 1990, Japan's Toyobo Company purchased the PBO patent technology from the Dow Chemical Company of the United States, and developed PBO fiber on Toyobo's equipment in 1991, which greatly increased the strength and modulus of PBO fiber to twice that of PPTA fiber.

[0005] PBO honeycomb paper is a high-performance bionic PBO structural component, which is also made up of hexagonal units. Compared with aramid fiber, the strength and modulus of PBO fiber are twice that of aramid 1414 fiber, and its decomposition temperature can reach 650°C, which is better than the decomposition temperature of para-aramid at 550°C. PBO fiber surpasses aramid fiber in many performance indicators, especially in high-end application fields, the potential of PBO fiber is more significant.

[0006] At present, honeycomb paper is mainly prepared by bonding and stretching. First, aramid paper and PBO paper are prepared using short-cut fibers and chromatography fibers. Then, these papers are used as raw materials to form the final honeycomb paper product through multiple processes such as gluing, hot pressing, trimming, stretching, shaping, dipping, drying, curing and slicing. However, the following problems exist in the preparation of honeycomb paper using the above method: 1. Imprecise structural control: During the stretching process, all honeycomb units are formed at the same time, and the structural shape of each unit cannot be accurately controlled, which can easily lead to over-stretching, under-stretching or even damage of some units, resulting in local defects and affecting the overall strength.

[0007] 2. Performance issues in high temperature environments: Since different layers are bonded together using adhesive strips, the adhesive will soften and fail in a high temperature environment, affecting the performance of honeycomb paper in a high temperature environment.

[0008] 3. Shape limitation: The bonding and stretching method can only produce flat honeycomb paper. When applied to curved surfaces or complex spaces, it needs to be spliced ​​or bonded through secondary processing, which cannot fully utilize the strength limit of honeycomb paper.

[0009] 4. Environmental issues: In order to fill the pores between coarse fibers and optimize load transfer, phenolic resin will be used in the dipping step, which will produce a large amount of toxic carcinogens such as formaldehyde and phenol, causing serious harm to the environment.

[0010] In summary, if a new honeycomb paper forming method can be proposed to achieve efficient preparation of high-quality, special-shaped fiber structural parts, it will be of great significance to improve the application defects of existing honeycomb paper. Summary of the invention

[0011] The purpose of the present invention is to overcome the defects and shortcomings of the prior art and to provide a method for integrated extrusion molding of high-performance nanofiber structural parts. The method mainly solves the problems that honeycomb paper prepared by the prior art is prone to local unit defects, single molding shape, viscose failure in high temperature environment, and great hazards in the production process.

[0012] Another object of the present invention is to provide an integrated extrusion molding equipment for high-performance nanofiber structural parts to realize the above method.

[0013] The purpose of the present invention can be achieved through the following technical solutions: A method for integrated extrusion molding of a high-performance nanofiber structural component comprises the following steps: (1) adding the nanofiber solution to a forced mixing and conveying device, so that the nanofiber solution is sheared and converted into a homogenized dispersion in the forced mixing and conveying device, and then the homogenized dispersion is injected into a molding mold through an extrusion die under the extrusion pressure provided by the forced mixing and conveying device; (2) immersing the entire molding mold in the reconstitution solution, and the homogenized dispersion injected into the molding mold undergoes solvent exchange with the reconstitution solution, so that the homogenized dispersion undergoes sol-gel conversion to form a nanofiber composite gel with a predetermined shape; (3) Washing and drying the nanofiber composite gel having a predetermined shape to obtain a nanofiber structural member.

[0014] The nanofiber solution is one of an aramid nanofiber solution, an aramid nanofiber composite solution, a PBO nanofiber solution and a PBO nanofiber composite solution.

[0015] The aramid nanofiber composite solution is a composite solution of an aramid nanofiber solution and a functional filler; the PBO nanofiber composite solution is a composite solution of a PBO nanofiber solution and a functional filler.

[0016] The functional filler can be a filler with mechanical strength, thermal stability, electrical conductivity, thermal conductivity or flame retardancy such as boron nitride nanosheets, graphene, graphene oxide, carbon nanotubes, silica nanoparticles, silver nanoparticles, polyacetylene, aramid staple fibers, etc. The aramid nanofiber solution and the PBO nanofiber solution are mixed with the functional filler to prepare an aramid nanofiber composite solution and a PBO nanofiber composite solution with specific properties, respectively.

[0017] As a preferred embodiment, in step (1), the molding die is pre-filled with a skeleton structure formed by a functional filler. The functional filler can be pre-filled in the molding die, and the skeleton structure can be pre-formed in the molding die by a method such as dry deposition.

[0018] In the step (1), the nanofiber solution is shear-mixed by a forced mixing and conveying device to form a more uniform and better dispersed homogenized dispersion, which has a certain fluidity at a set temperature. The aramid staple fibers can be pre-formed into an aramid staple fiber skeleton structure in the molding die by methods such as drying and deposition. The fluid nanofiber solution can be filled into the gaps in the aramid staple fiber skeleton structure under the pressure of the device to form a dense structure.

[0019] The reconstruction solution is divided into two types. For aramid nanofiber solution and aramid nanofiber composite solution, the reconstruction solution uses a proton donor solution with proton supply ability. Adding the proton donor solution to the aramid nanofiber solution or the aramid nanofiber composite solution can reconstruct its molecular chain and form a self-supporting gel with a certain strength; for PBO nanofiber solution and PBO nanofiber composite solution, the reconstruction solution uses a proton acceptor solution with deprotonation ability. Adding the proton acceptor solution to the PBO nanofiber solution or the PBO nanofiber composite solution can reconstruct its molecular chain and form a self-supporting gel with a certain strength. By changing the concentration and type of the proton donor solution / proton acceptor solution, nanofiber composite gels with different microstructures can be obtained.

[0020] The solvent exchange between the homogenized dispersion and the reconstitution solution is performed after the completion of step (1) or simultaneously with step (1). In step (2), the solvent exchange process can be completed by transferring the molding die to the reconstitution solution after the extrusion is completed, or by directly extruding the solution into the molding die that has been soaked in the reconstitution solution.

[0021] A high-performance nanofiber structural component integrated extrusion molding equipment is used to implement the high-performance nanofiber structural component integrated extrusion molding method of the present invention, including a forced mixing and conveying device, an extrusion die head and a molding mold. The input end of the forced mixing and conveying device is provided with a feed port, and the extrusion die head is fixedly installed at the output end of the forced mixing and conveying device and connected to the molding mold through a pipeline.

[0022] The forced mixing and conveying device may adopt a mixing and conveying system formed by a positive displacement pump and a mixer, a multi-rotor mixing and conveying system or a single-rotor mixing and conveying system.

[0023] The forced mixing and conveying device is a mechanism with positive displacement conveying capability, which can be realized by using a mixing and conveying system that is a combination of a positive displacement pump and a mixer, or by using a multi-rotor mixing and conveying system or a single-rotor mixing and conveying system that has both conveying and mixing functions. Different mold filling speeds and filling effects can be achieved by selecting different types of mixing and conveying systems and changing the extrusion speed and extrusion pressure of the mixing and conveying systems.

[0024] The positive displacement pump can be a reciprocating pump, a diaphragm pump, a gear pump, a screw pump, a plunger pump or a vane pump; the mixer can be a dynamic mixer or a static mixer, the dynamic mixer includes a multi-stage rotating mechanism, and the static mixer is composed of a multi-stage mixing channel. By using different types of positive displacement pumps and mixers, and adjusting the speed and mixing stages of the mixer, uniform dispersion of filler systems with different concentrations and functions can be achieved.

[0025] Select a suitable mixing and conveying system as a forced mixing and conveying device according to specific application requirements, material properties and expected product performance.

[0026] The extrusion die can be a single-channel extrusion die or a multi-channel extrusion die.

[0027] The extrusion die head is provided with a plurality of discharge ports, and the molding die is provided with a feed port. The number of the discharge ports corresponds to the feed port, and the discharge ports are connected with the feed port through pipelines.

[0028] By changing the number of feed ports and discharge ports, simultaneous extrusion in multiple channels and directions can be achieved.

[0029] The molding mold comprises a mold cavity and a cover plate, and both the mold cavity and the cover plate are provided with a pore structure. Solvent exchange between the nanofiber solution and the reconstructed solution is achieved through the pore structure.

[0030] A plurality of filling columns are distributed in the mold cavity, and the filling columns are hollow structures, so as to increase the dissolution exchange area between the nanofiber solution and the reconstructed solution.

[0031] By changing the cross-sectional shape, spatial shape and distance between adjacent filling columns, fiber structures with different pore structures and different pore densities can be prepared.

[0032] Furthermore, by designing special curved molds and changing the density or shape of filling columns in different mold areas, fiber structural parts with complex spatial topological structures can be prepared.

[0033] As a preferred embodiment, both the forced mixing and conveying device and the extrusion die are provided with temperature control devices; the forced mixing and conveying device and the extrusion die are connected by a flange; the discharge port of the extrusion die and the pipeline, and the pipeline and the feed port of the molding mold are connected by clamps, and the clamp connections are sealed with rubber rings.

[0034] The principle of the present invention is that the nanofibers prepared by the deprotonation method exist in the form of a polyanion solution, and amide hydrogen is missing from their molecular chains. Adding a proton donor to the nanofiber solution causes the structure of its molecular chain to be reconstructed, and then the nanofibers with restored complete molecular structures will generate intermolecular hydrogen bonds and cross-link and accumulate with each other, eventually forming a gel-like product with a microscopic three-dimensional network structure. Using this sol-gel conversion principle, the efficient preparation of complex fiber structures can be achieved.

[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The integrated extrusion molding method of the high-performance nanofiber structural member of the present invention is prepared by using the solution filling principle. By controlling the structure of the filling column in the mold, the precise control of the single hexagonal unit structure can be achieved, which is conducive to forming a fiber honeycomb paper with uniform size structure and few unit defects.

[0036] 2. The integrated extrusion molding method of the high-performance nanofiber structural parts of the present invention is prepared based on the sol-gel conversion method, which can directly form an integrated fiber honeycomb paper with a predetermined shape without the need for additional shaping or bonding. The preparation process is simple and the structural strength consistency is good at high temperatures.

[0037] 3. The integrated extrusion molding equipment for high-performance nanofiber structural parts of the present invention can design molds according to actual scenarios and directly prepare fiber structural parts with complex spatial structures without splicing or secondary processing. It can achieve local reinforcement of high stress areas by changing the local density of filling columns in the mold based on the actual force distribution of the structural parts, making the strength design of the entire fiber structural part more balanced.

[0038] 4. The high-performance nanofiber structural component integrated extrusion molding method of the present invention has high density and good load transfer performance, does not require dipping and strengthening, has less pollution, and can achieve regulation of its microscopic pore structure through different reconstruction methods, which is conducive to loading different functional fillers.

[0039] The integrated extrusion molding method for high-performance nanofiber structural parts provided by the present invention has the advantages of fewer steps and less environmental harm. The proposed integrated extrusion molding equipment for nanofiber structural parts has a simple structure and wide applicability, and can realize the efficient preparation of functional nanofiber structural parts with complex spatial structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 1 is a schematic diagram of the overall structure of the integrated extrusion molding equipment for nanofiber structural parts in Example 1 of the present invention; Figure 2 It is a schematic diagram of the sol-gel conversion and drying steps in the integrated extrusion molding method of the nanofiber structure of the present invention; Figure 3 is a schematic structural diagram of a static mixer in Example 1 of the present invention; Figure 4 is a schematic structural diagram of the aramid honeycomb paper having a uniform hexagonal structure in Example 1 of the present invention; Figure 5 is a cross-sectional view of the aramid honeycomb paper having a uniform hexagonal structure in Example 1 of the present invention; Figure 6 is a schematic diagram of the overall structure of the integrated extrusion molding equipment for nanofiber structural parts in Example 3 of the present invention; Figure 7 is a schematic structural diagram of aramid honeycomb paper having the same density in Example 3 of the present invention; Figure 8 is a cross-sectional view of the aramid honeycomb paper having the same density in Example 3 of the present invention; Fig. 9 is a schematic structural diagram of a dynamic mixer in Example 4 of the present invention; Fig.10 Schematic diagram of the process of multi-channel extrusion die head with multiple discharge ports performing multi-directional simultaneous extrusion filling in Example 4 of the present invention; Fig.11 is a schematic structural diagram of the aramid honeycomb paper having a spatial topological structure in Example 4 of the present invention; Fig.12 is a cross-sectional view of the aramid honeycomb paper having a spatial topological structure in Example 4 of the present invention; Wherein: 1: push rod, 2: positive displacement pump, 3: hopper, 4: mixer, 5: temperature control device, 6: extrusion die head, 7: pipeline, 8: mold cavity, 9: cover plate, 10: barrel, 11: rotor, 12: first extrusion direction, 13: second extrusion direction, 14: third extrusion direction, 15: fourth extrusion direction. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0042] Example 1 like Figure 1 and Figure 2 As shown, a high-performance nanofiber structural component integrated extrusion molding method mainly includes the following steps: (1) First, a pure aramid nanofiber solution with a mass concentration of 1.5wt% is added into the cavity of a push rod plunger pump through a hopper. After the cavity of the push rod plunger pump is filled with the pure aramid nanofiber solution, the push rod is started to push the pure aramid nanofiber solution through an SK-type static mixer with a single flow channel with a torsion angle of 120 degrees and a flow channel number of 4 at a speed of 8mm / s under the conditions of an extrusion pressure of 3.5MPa and an extrusion temperature of 60°C. Then, the solution is injected into a flat honeycomb mold through a single-flow extrusion die head through a pipeline, so that the mold cavity is completely filled; The flat honeycomb mold has a pore structure with a pore size of 150 microns; and a filling column is arranged in the mold, the angle of the filling column cross section changes by 120 degrees, and the gap between adjacent filling columns is 1.6 mm; (2) Then, the flat honeycomb mold is removed and immersed in an acetic acid solution with a volume concentration of 40 vol% (such as Figure 5As shown), the pure aramid nanofiber solution is subjected to solvent exchange with the acetic acid solution, and the solution is allowed to stand for a certain period of time until the reconstruction is completed; (3) Finally, rinse the flat honeycomb mold in clean water and place it in an oven at a certain temperature to dry it before taking it out.

[0043] In this embodiment, the high-performance nanofiber structural component integrated extrusion molding equipment implementing the above method includes a forced mixing and conveying device, an extrusion die head 6 and a molding mold. The forced mixing and conveying device adopts a mixing and conveying system formed by a positive displacement pump 2 and a mixer 4, wherein the positive displacement pump adopts a push rod plunger pump, and a push rod 1 is concentrically installed in the cavity of the positive displacement pump, and the two can move relative to each other. A feed port is provided at the input end of the positive displacement pump, and a hopper 3 is installed on the feed port; Figure 3 As shown, the mixer adopts a static mixer composed of a multi-stage mixing channel, which is installed behind the positive displacement pump and connected by bolts; the extrusion die is fixedly installed at the output end of the static mixer and connected to the molding die through a pipeline; the molding die includes a mold cavity 8 and a cover plate 9, the cover plate is combined with the mold cavity to form a closed extrusion cavity space, and the mold cavity and the cover plate are both provided with a pore structure; the temperature control device 5 is distributed on the positive displacement pump, the mixer and the extrusion die to maintain the extrusion temperature.

[0044] In this embodiment, a pure aramid nanofiber solution is used as the nanofiber solution, and the mass concentration thereof is 1-2.5wt%, and the preferred value is 1.5wt%.

[0045] A push rod plunger pump is used as the source of the extrusion pressure, wherein the push rod speed is 0.5-20 mm / s, preferably 8 mm / s, and the extrusion pressure in the cavity of the pressure device is 2.3-5.5 MPa, preferably 3.5 MPa.

[0046] The mixer uses Figure 4 The SK type static mixer shown mixes the nanofiber solution and achieves sufficient mixing of the solution through its reverse twisted flow channels, the twist angle of a single flow channel is 90-180 degrees, preferably 120 degrees, and the number of flow channel stages is 2-10, preferably 4.

[0047] The temperature control device adopts a thermocouple, and the extrusion temperature is 30-120°C, preferably 50-70°C.

[0048] An acetic acid solution having proton donating capability is used as the reconstitution solution, and its volume concentration is 15-80 vol%, preferably 30-50 vol%.

[0049] A flat honeycomb mold is used as an extrusion molding mold. The mold cavity and the cover plate are both provided with a pore structure for realizing solvent exchange, and the pore size is 20-310 microns, and the preferred value is 120-180 microns.

[0050] The filling columns distributed inside the mold cavity have equal cross-sectional sizes in the height direction, and their cross-sections are hexagonal. The angles of their corners vary from 30 to 150 degrees, preferably 120 degrees. The gap between adjacent filling columns is 0.4 to 5 mm, preferably 1.6 mm.

[0051] like Figure 4 and Figure 5 As shown, by using the above method and equipment, aramid honeycomb paper with a uniform hexagonal structure can be quickly prepared in an integrated manner, with a bulk density of 20-70 kg / m3 and a hexagonal plane compression strength of 172-200 MPa.

[0052] Example 2 Compared with Example 1, the difference is that the nanofiber solution adopts a PBO nanofiber solution, and the reconstructed solution adopts a proton acceptor solution with deprotonation ability.

[0053] A method for integrated extrusion molding of high-performance nanofiber structural parts mainly includes the following steps: (1) First, a pure PBO nanofiber solution with a mass concentration of 1.5wt% is added into the cavity of a push rod plunger pump through a hopper. After the cavity of the push rod plunger pump is filled with the pure aramid nanofiber solution, the push rod is started to push the pure PBO nanofiber solution through an SK-type static mixer with a single flow channel with a torsion angle of 120 degrees and a flow channel number of 4 at a speed of 8mm / s under the conditions of an extrusion pressure of 3.5MPa and an extrusion temperature of 60°C. Then, the solution is injected into a flat honeycomb mold through a single-flow extrusion die head through a pipeline, so that the mold cavity is completely filled; (2) Then, the flat honeycomb mold is removed and immersed in an isopropanol solution with a volume concentration of 45 vol% (such as Figure 5 As shown), the pure PBO nanofiber solution and the isopropanol solution are subjected to solvent exchange, and the solution is allowed to stand for a certain period of time until the reconstruction is completed; (3) Finally, rinse the flat honeycomb mold in clean water and place it in an oven at a certain temperature to dry it before taking it out.

[0054] In this embodiment, pure PBO nanofiber solution is used as the nanofiber solution, and its mass concentration is 1-2.5wt%, preferably 1.5wt%.

[0055] An isopropanol solution having deprotonation ability is used as the reconstitution solution, and its volume concentration is 15-80 vol%, preferably 30-50 vol%.

[0056] By using the above method and equipment, PBO honeycomb paper with a uniform hexagonal structure can be quickly prepared in an integrated manner, such as Figure 5 As shown, its bulk density is 45-70kg / m3 and its hexagonal plane compressive strength is 200-250MPa.

[0057] The parts not mentioned in this embodiment are the same as those in Embodiment 1.

[0058] Example 3 Compared with Example 1, the differences are: the nanofiber solution adopts an aramid nanofiber composite solution mixed with an aramid nanofiber solution and a functional filler, the forced mixing and conveying device adopts a double-rotor mixing and conveying system, and the molding mold adopts a honeycomb mold with different local densities.

[0059] A method for integrated extrusion molding of high-performance nanofiber structural parts mainly includes the following steps: (1) First, an aramid nanofiber composite solution obtained by mixing an aramid nanofiber solution with a mass concentration of 1 wt% and boron nitride nanosheets is added into the cavity of a dual-rotor mixing and conveying system through a hopper. After the cavity of the dual-rotor mixing and conveying system is filled with the aramid nanofiber composite solution, the rotors are started and run at a speed of 500 rpm, so that the aramid nanofiber solution is fully mixed with the boron nitride nanosheets under the action of the dual rotors. At the same time, the aramid nanofiber composite solution is pushed through an SK-type static mixer with a single flow channel having a torsion angle of 120 degrees and a flow channel number of 4 at a speed of 8 mm / s under the conditions of an extrusion pressure of 22 MPa and an extrusion temperature of 50°C, and then injected into a honeycomb mold with different local densities through a single-channel extrusion die head through a pipeline, so that the mold cavity is completely filled; The honeycomb mold with different local densities has a pore structure with a pore size of 150 microns; and a filling column is arranged in the mold, the cross section of which is a regular hexagon, and the gap size between adjacent filling columns is divided into three levels of 4mm, 2mm, and 1mm; (2) Then, the honeycomb molds with different local densities were removed and immersed in an acetic acid solution with a volume concentration of 40 vol% (e.g. Figure 5 As shown), the aramid nanofiber composite solution and the acetic acid solution undergo solvent exchange, and the solution is allowed to stand for a certain period of time until reconstruction is completed; (3) Finally, the honeycomb molds with different local densities are rinsed in clean water and placed in an oven at a certain temperature to dry before being taken out.

[0060] In this embodiment, the high-performance nanofiber structural component integrated extrusion molding equipment for implementing the above method includes a forced mixing and conveying device, an extrusion die head and a molding die, such as Figure 6As shown, the forced mixing and conveying device adopts a multi-rotor mixing and conveying system, wherein the multi-rotor mixing and conveying system is a double-rotor mixing and conveying system composed of two mutually meshing rotors 11 and a barrel 10, the two rotors can move relative to each other, and a feed port is provided at the input end of the barrel, and a hopper is installed on the feed port; the extrusion die head is fixedly installed at the output end of the barrel and is connected to the molding mold through a pipeline; the molding mold includes a mold cavity and a cover plate, the cover plate is engaged with the mold cavity to form a closed extrusion cavity space, and a pore structure is provided on the mold cavity and the cover plate; the temperature control device is distributed on the barrel and the extrusion die head to maintain the extrusion temperature.

[0061] In this embodiment, an aramid nanofiber composite solution prepared by mixing an aramid nanofiber solution with boron nitride nanosheets is used as the nanofiber solution. The mass concentration of the aramid nanofiber solution is 1.5-2wt%, preferably 1wt%.

[0062] A dual-rotor mixing and conveying system consisting of two mutually meshing rotors and a barrel is used as the source of extrusion pressure to achieve extrusion pressure and mixing effects at the same time, wherein the rotor speed is 100-1000rpm, preferably 500rpm, and the extrusion pressure in the pressure device cavity is 4.3-50MPa, preferably 17.7-28MPa.

[0063] The temperature control device adopts a thermocouple, and the extrusion temperature is 30-90°C, preferably 40-60°C.

[0064] An acetic acid solution having proton donating capability is used as the reconstitution solution, and its volume concentration is 15-80 vol%, preferably 30-50 vol%.

[0065] A honeycomb mold with different local densities is used as an extrusion molding mold. The cross-section of the filling column inside the mold cavity is a regular hexagon. The gaps between adjacent filling columns are divided into three levels: 4mm, 2mm, and 1mm. Hexagonal units with different thicknesses can be formed on the same aramid-boron nitride nano honeycomb paper.

[0066] like Figure 7 and Figure 8 As shown, by using the above method and equipment, aramid-boron nitride nano honeycomb paper with high thermal conductivity and different local thickness can be quickly prepared in an integrated manner, and its in-plane thermal conductivity is 1.8-4.1 W / (m•K).

[0067] The parts not mentioned in this embodiment are the same as those in Embodiment 1.

[0068] Example 4 Compared with Example 1, the differences are: the mixer adopts a dynamic mixer including a multi-stage rotating mechanism, the extrusion die adopts a multi-channel extrusion die with multiple discharge ports, the molding mold adopts a honeycomb mold with a spatial topological structure, and the reconstructed solution adopts a formic acid solution.

[0069] A method for integrated extrusion molding of high-performance nanofiber structural parts mainly includes the following steps: (1) First, a pure aramid nanofiber solution with a mass concentration of 2.5wt% is added into the cavity of a push rod plunger pump through a hopper. After the cavity of the push rod plunger pump is filled with the pure aramid nanofiber solution, the push rod is started to push the pure aramid nanofiber solution through a multi-stage dynamic mixer with a mixing speed of 4500rpm and a mixing stage of 2 under the conditions of an extrusion pressure of 3.5MPa and an extrusion temperature of 70°C, and then injected into a honeycomb mold with a spatial topological structure through a pipeline through a multi-channel extrusion die head, so that the mold cavity is completely filled; The topological shape of the honeycomb mold with a spatial topological structure is designed according to the contour of the current aircraft radome; the mold has a pore structure with a pore size of 150 microns, a filling column is arranged in the mold, the cross section of the filling column is a regular hexagon, the gap between adjacent filling columns is 1.6mm, and the thickness of the mold cavity is 12mm; feed ports are arranged around the mold, and a multi-channel extrusion die head is used to realize simultaneous extrusion in the first extrusion direction 12, the second extrusion direction 13, the third extrusion direction 14, and the fourth extrusion direction 15 (such as Fig.10 shown); (2) then removing the honeycomb mold with the spatial topological structure and immersing it in a formic acid solution with a volume concentration of 48 vol% to allow the pure aramid nanofiber solution to undergo solvent exchange with the formic acid solution, and then standing for a certain period of time until the reconstruction is completed; (3) Finally, the honeycomb mold with a spatial topological structure is rinsed in clean water and placed in an oven at a certain temperature to dry before being taken out.

[0070] like Figure 1 As shown, in this embodiment, the high-performance nanofiber structural component integrated extrusion molding equipment implementing the above method includes a forced mixing and conveying device, an extrusion die head and a molding mold. The forced mixing and conveying device adopts a mixing and conveying system formed by a positive displacement pump and a mixer, wherein the positive displacement pump adopts a push rod plunger pump, a push rod is concentrically installed in the cavity of the positive displacement pump, and the two can move relative to each other, and a feed port is provided at the input end of the positive displacement pump, and a hopper is installed on the feed port; Fig. 9As shown, the mixer adopts a dynamic mixer including a multi-stage rotating mechanism, which is installed behind a positive displacement pump and connected by bolts; the extrusion die is fixedly installed at the output end of the dynamic mixer and connected to the molding die through a pipeline; the molding die includes a mold cavity and a cover plate, the cover plate is engaged with the mold cavity to form a closed extrusion cavity space, and a pore structure is provided on the mold cavity and the cover plate; the temperature control device is distributed on the positive displacement pump, the mixer and the extrusion die to maintain the extrusion temperature.

[0071] In this embodiment, a pure aramid nanofiber solution is used as the nanofiber solution, and the mass concentration thereof is 1.5-4wt%, and the preferred value is 2.5wt%.

[0072] The mixer uses a multi-stage dynamic mixer to mix the nanofiber solution, and the solution is fully mixed through its multi-stage rotating mechanism. The mixing speed is 3000-6000rpm, the selected value is 4000-5000rpm, the mixing level is 1-4, and the preferred value is 2.

[0073] The temperature control device adopts a thermocouple, and the extrusion temperature is 50-110°C, and the preferred value is 62-77°C.

[0074] A formic acid solution having proton donating capability is used as the reconstitution solution, and its volume concentration is 30-70 vol %, preferably 40-55 vol %.

[0075] A honeycomb mold with a spatial topological structure is used as an extrusion molding mold, and the thickness of the mold cavity is 5-30 mm, and the preferred value is 12 mm.

[0076] like Fig.11 and Fig.12 As shown, by using the above method and equipment, aramid honeycomb paper with a spatial topological structure can be quickly prepared in an integrated manner.

[0077] The parts not mentioned in this embodiment are the same as those in Embodiment 1.

[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for integrated extrusion molding of high-performance nanofiber structural parts, characterized in that: The following steps are involved: (1) adding the nanofiber solution to a forced mixing and conveying device, so that the nanofiber solution is sheared and converted into a homogenized dispersion in the forced mixing and conveying device, and then the homogenized dispersion is injected into a molding mold through an extrusion die under the extrusion pressure provided by the forced mixing and conveying device; (2) immersing the entire molding mold in the reconstitution solution, and the homogenized dispersion injected into the molding mold undergoes solvent exchange with the reconstitution solution, so that the homogenized dispersion undergoes sol-gel conversion to form a nanofiber composite gel with a predetermined shape; (3) Washing and drying the nanofiber composite gel having a predetermined shape to obtain a nanofiber structural member.

2. The method for integrated extrusion molding of a high-performance nanofiber structural component according to claim 1, characterized in that: The nanofiber solution is an aramid nanofiber solution, an aramid nanofiber composite solution, a PBO nanofiber solution or a PBO nanofiber composite solution.

3. The method for integrated extrusion molding of a high-performance nanofiber structural component according to claim 2, characterized in that: For the aramid nanofiber solution and the aramid nanofiber composite solution, the reconstructed solution uses a proton donor solution with proton donating ability; For the PBO nanofiber solution and the PBO nanofiber composite solution, the reconstructed solution adopts a proton acceptor solution having deprotonation ability.

4. The method for integrated extrusion molding of a high-performance nanofiber structural component according to claim 1, characterized in that: In the step (1), the molding die is pre-filled with a skeleton structure formed by a functional filler.

5. An integrated extrusion molding equipment for high-performance nanofiber structural parts, implementing the integrated extrusion molding method for high-performance nanofiber structural parts as described in any one of claims 1 to 4, characterized in that: It includes a forced mixing and conveying device, an extrusion die head and a forming mold. The input end of the forced mixing and conveying device is provided with a feed port, and the extrusion die head is fixedly installed at the output end of the forced mixing and conveying device and connected with the forming mold through a pipeline.

6. The high-performance nanofiber structural component integrated extrusion molding equipment according to claim 5, characterized in that: The forced mixing and conveying device adopts a mixing and conveying system formed by combining a positive displacement pump and a mixer, a multi-rotor mixing and conveying system or a single-rotor mixing and conveying system.

7. The high-performance nanofiber structural component integrated extrusion molding equipment according to claim 6, characterized in that: The positive displacement pump adopts a reciprocating pump, a diaphragm pump, a gear pump, a screw pump, a plunger pump or a vane pump; the mixer adopts a dynamic mixer or a static mixer, the dynamic mixer includes a multi-stage rotating mechanism, and the static mixer consists of a multi-stage mixing flow channel.

8. The high-performance nanofiber structural component integrated extrusion molding equipment according to claim 5, characterized in that: The extrusion die head adopts a single-flow extrusion die head or a multi-flow extrusion die head.

9. The high-performance nanofiber structural component integrated extrusion molding equipment according to claim 5, characterized in that: The molding die comprises a die cavity and a cover plate, and both the die cavity and the cover plate are provided with a pore structure.

10. The high-performance nanofiber structural component integrated extrusion molding equipment according to claim 9, characterized in that: A plurality of filling columns are distributed in the mold cavity, and the filling columns are hollow structures.

Citation Information

Patent Citations

  • Polymer melt pulsating deformation driving method and device

    CN104494062A

  • Cellulose aerogel and preparation method for hybrid aerogel thereof

    CN105017555A

  • Method for producing an aerogel material

    CN107428545A

  • Method for preparing aramid honeycomb through direct forming

    CN111775502A

  • High-performance bulk aramid nanofiber aerogel as well as preparation method and application thereof

    CN112980044A